GALICIAN CASTLE IN THE LIGHT OF THE INVENTORY OF THE GALICIAN STAROSTVO IN 1767 - GOSZCZYŃSKI, Artur (Halych. Scientific work collection, 2024)
The castle in Galych had been one of the most important stronholds in the Pokuttya region. This settlement has history reaching the middle ages. Developed over the years had been towering and was the main defence point of nearby territories. Due to Tatar invasions, the castle was destroyed several times. In a half of XVII century, thanks to Andrzej Potocki who was the galicianstarosta, the castle was completely renovated. Greatness of the stronghold did not last too long. It was seriously damaged during a war between Republic of Poland and Ottoman Empire by the latter in 1676. The scale of the castle fall among hundreds of years excellently shows inventory of Galych District Head from 1767 containing description of the stronghold. It is described as extremely neglected building demanding immediately works, what also was emphasised by the author of the text several times.